Apocalypse, Authority, and Allegiance: Interpreting Symbols and Revelation in Mozambique. (April 2021) - Howell, Alan; Best, Garrett
Proper interpretations of symbols of authority are important for navigating both our cultural settings and the contours of Scripture. This paper looks at the ways the Book of Revelation contrasts images of competing authoritative kings, asking the question, who is worthy of worship, Caesar or Christ? In the African Folk-Islamic context of the Makua-Metto people of Mozambique, familiar national and traditional symbols of authority provide a framework for a robust reading of John's Apocalypse.